2016
DOI: 10.1001/journalofethics.2016.18.8.ecas1-1608
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Questions about Platelet Transfusions at the End of Life

Abstract: This case of platelet transfusion in palliative care illustrates a common dilemma in transfusion medicine: approval of the use of a scarce, yet potentially life-saving, resource. As in this case, these decisions often involve seriously ill patients with acute needs and evolving goals of care. The use of resources to treat the patient at hand must be balanced against maintaining adequate resources to treat future patients. In this setting, the ethical principles of beneficence and social justice are in conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Some argue that use of scarce resources such as blood must be balanced against maintaining adequate resources to treat future patients, thus putting the ethical principles of beneficence and social justice in conflict. 18,19 Use of blood transfusion at the end of life may have an effect on survival of patients with cancer. A review of red blood cell transfusions in a palliative care unit in Adelaide, Australia, found that among patients, blood transfusions led to subjective improvement in a majority of recipients, although this correlated poorly with objective scale-based measures.…”
Section: Discussionmentioning
confidence: 99%
“…Some argue that use of scarce resources such as blood must be balanced against maintaining adequate resources to treat future patients, thus putting the ethical principles of beneficence and social justice in conflict. 18,19 Use of blood transfusion at the end of life may have an effect on survival of patients with cancer. A review of red blood cell transfusions in a palliative care unit in Adelaide, Australia, found that among patients, blood transfusions led to subjective improvement in a majority of recipients, although this correlated poorly with objective scale-based measures.…”
Section: Discussionmentioning
confidence: 99%